Hidradenitis suppurativa and the metabolic syndrome - ERGUN, SAFİYE ATLAS TÜLİN (ELSEVIER SCIENCE INC, 2018)
The association of the metabolic syndrome (MetS) and its components with immune-mediated chronic inflammatory disorders has attracted much interest within the last two decades. In addition to the well-established association of psoriasis with MetS, recent data point to an association between MetS and hidradenitis suppurativa, as well. The association of hidradenitis suppurativa with MetS and its components, such as diabetes, obesity, and dyslipidemia, has been consistently identified in controlled studies. This relationship is not only limited to older individuals but also applicable to younger patients and those with mild disease. This review documents the link between these disorders and discusses its practical implications, mainly highlighting the importance of prevention and routine screening for early diagnosis to prevent cardiovascular-related morbidity. (C) 2018 Elsevier Inc. Ail rights reserved.
Keywords: CARDIOVASCULAR-DISEASE; PREVALENCE; PSORIASIS; RISK; MORTALITY; ARTHRITIS; LESIONS; ACNE